Funeral of Kautsky at Driehuis-Westerveld, Amsterdam. Left of the flag-bearer: (from right to left) Hilferding, Adler, Hertz
Funeral of Kautsky at Driehuis-Westerveld, Amsterdam. Left of the flag-bearer: (from right to left) Hilferding, Adler, Hertz.